The Relationship Between Self-Concept and Students’ Mathematical Connection Ability - Ulfah, Elia Damayantie; Supratman, Supratman; Patmawati, Hetty (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
This study is conducted to explore how self-concept correlates with mathematical connection skills among eight-grade students at SMPN 14 Tasikmalaya. The research method used is a survey method with a deskriptive quantitative approach. The population used in this study was all eight-grade students at SMPN 14 Tasikmalaya. This study applied simple random sampling, resulting in a sample of 36 students. Data collection was conducted through the distribution of self-concept questionnaires and mathematical connection ability tests. The research instruments used were self-concept questionnaires and essay questions to measure mathematical connection ability. The data analysis technique used to test the hypothesis was the Pearson product-moment correlation test, preceded by prerequisite analysis tests, namely normality and linearity tests. The results of the data analysis showed that there was a positive and significant correlation between self-concept and students' mathematical connection abilities. Students' self-concept was categorized as moderate, and their mathematical connection abilities was also in the moderate category. These findings indicate that the more positive the self-concept of students, the higher their mathematical connection abilities